SPATIAL PATTERN OF URBAN HEAT SIGNATURE AND ITS IMPACT ON PAMOYANAN VILLAGE, CIANJUR DISTRICT - Sunukanto, V S; Semedi, Jarot Mulyo; Ash Shidiq, Iqbal Putut; Kamarudin, Norizah; Wibowo, Adi (UI Scholars Hub, 2021)
According to the World Bank's Climate Change Knowledge Portal in 2020, the increase in annual temperature in Indonesia, which tends to rise by 0.3°C, is consistent with the Urban Heat phenomenon. Population growth and shifting land cover contribute to annual temperature fluctuations by reducing the amount of vegetated land. The increase in temperature in the urban environment has particular impacts on the community in terms of environmental changes. The term